Nuts: Where We Are and Where We Are Going in Research. Proceedings from the NUTS 2022 International Conference - Salas-Salvadó, Jordi; Ros, Emilio; Sabaté, Joan; Nishi, Stephanie (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Humans have eaten nuts for thousands of years, yet their consumption was discouraged just a few decades ago due to their high-fat content. This perspective began to change in the early 1990s due to seminal publications from the Adventist Health Study, which showed that nut consumption significantly improved heart health-related outcomes. Many randomized clinical trials, epidemiological studies, and in vitro/in vivo mechanistic studies have since explored the role of eating nuts and its relation to health. Similarly, dried fruits have been scrutinized due to their concentrated sugar content despite their non-sodium micronutrient and fiber density. Due to accumulating evidence on nut and dried fruit intake and health outcomes, an international scientific meeting was organized for leading experts to examine and recapitulate in detail what is well known and established and what avenues of knowledge are still lacking in nut and dried fruit research. These findings highlight the beneficial health potentials of nuts for researchers, health professionals, other stakeholders, and the public while simultaneously pinpointing areas for further investigation to continue informing and guiding health practices and policies.